2020
DOI: 10.3390/geosciences10010027
|View full text |Cite
|
Sign up to set email alerts
|

Geoparks and Education: UNESCO Global Geopark Villuercas-Ibores-Jara as a Case Study in Spain

Abstract: The UNESCO Global Geoparks is a good didactic instrument that allows teaching territorial elements in transversal way. The geopark provides a means to address the teaching-learning process of both cultural values and natural values, including geology. This paper aims to highlight the educational activities that have emerged from the Villuercas UNESCO Global Geopark. For this purpose, a qualitative methodology based on document analysis and fieldwork has been used. Through a system of categories, we have analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 58 publications
0
9
0
1
Order By: Relevance
“…Edukasi menjadi kunci utama untuk meningkatkan kesadaran dan apresiasi yang menjadi salah satu tujuan utama geopark (Henriques & Brilha, 2017). Sebagai sarana belajar, geopark mampu menyediakan metode pembelajaran yang riil dan dapat diakses oleh semua kalangan serta dapat berjalan dalam bentuk formal maupun informal (Eder & Patzak, 2004;Álvarez, 2020) Upaya membangun pemahaman tersebut dilakukan dengan penyediaan geoinformasi yang menjadi dasar-dasarnya (Azman et al, 2010).…”
Section: Pendahuluanunclassified
“…Edukasi menjadi kunci utama untuk meningkatkan kesadaran dan apresiasi yang menjadi salah satu tujuan utama geopark (Henriques & Brilha, 2017). Sebagai sarana belajar, geopark mampu menyediakan metode pembelajaran yang riil dan dapat diakses oleh semua kalangan serta dapat berjalan dalam bentuk formal maupun informal (Eder & Patzak, 2004;Álvarez, 2020) Upaya membangun pemahaman tersebut dilakukan dengan penyediaan geoinformasi yang menjadi dasar-dasarnya (Azman et al, 2010).…”
Section: Pendahuluanunclassified
“…The relevance of environmental care and the need to create quality education accessible for everyone have marked the plans that, since the approval by the UN Member States of the 2030 Agenda for the Sustainable Development Goals, have evolved to reach very interesting models that are continuously contributing to these objectives (Rosado-González et al 2020 , and references therein). Within these projects, the UNESCO Global Geoparks have created their own formula to support the SDGs effectively and become authentic educational territories by and for society (Fernández-Álvarez 2020 ). As defined by UNESCO ( 2022 ), “UNESCO Global Geoparks are single, unified geographical areas where sites and landscapes of international geological significance are managed with a holistic concept of protection, education and sustainable development” they work every day to contribute the SDGs in a sustainable way from the educational field (Henriques et al 2012 ; Rosado-González et al 2020 ; Silva 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Nowlan [13] believe that geoparks should provide opportunities for public education of geological knowledge. Álvarez [14] considers that geopark is a good teaching tool to promote the popularization of geological knowledge through the geopark's educational and tourist infrastructures. Shu et al [15] took Danxia geoheritage as an example, and suggested that we should promote geoconservation by combining public education and geological practice, so that we can finally implement the sustainable development of resources.…”
Section: Introductionmentioning
confidence: 99%